Hand eczema: epidemiology, prognosis and prevention. (20th December 2019) - Agner, T.; Elsner, P.
Abstract: Hand eczema (HE) is a heterogeneous and often chronic disease located to the hands and wrist, and frequently associated with eczema on the feet. The aetiology is diverse, and the eczema may present with a variety of clinical symptoms. Acute and chronic stages appear; severity varies from mild to moderate and severe, and flares may be frequently recurrent or rare. The divergent aetiology and varied morphology of HE is sometimes tricky and may be challenging to the dermatologist. This review has focus on epidemiology, prognosis and prevention of HE, and intends to point towards some practical advice on how to diagnose, inform and guide HE patients.